Peningkatan Kapasitas Guru Paud dalam Mengembangkan Teknologi Pembelajaran di Kota Bula Seram Bagian Timur - Lokollo, Lamberthus Johannes J; Sahalessy, Arnold; Tuarissa, Yandry (Jurnal Pengabdian Arumbai, 2023)
Early childhood education (PAUD) is the process of nurturing children from birth to six years old to prepare their physical and mental growth for formal education. The age range of 0-6 years is considered a golden period, significantly influencing future development. Therefore, early childhood education plays a crucial role in supporting a child's growth. However, the limited use of learning technology often hampers innovation in PAUD education. The development of effective, student-centered, and interactive learning technology is essential to enhance educational quality. Key principles such as efficiency, interactivity, and teacher engagement must be considered. This community service program aims to improve PAUD teachers' understanding and implementation of learning technology aligned with the current PAUD curriculum in Bula City. The methods used include socialization and interactive discussions. The program was scheduled for July 2023, focusing on developing learning media for PAUD teachers. The long-term plan involves all PAUD teachers in Bula City, East Seram, with the goal of enhancing their capacity in learning technology. The program activities included face-to-face sessions, demonstrations, and hands-on training in learning media. A total of 26 PAUD teachers participated, covering topics such as teacher orientation, media theory, and learning technology. Despite time constraints, the program successfully improved teachers' knowledge and skills. The evaluation results were positive, showing significant benefits for the quality of learning.